Supplementary material from Better the devil you know: common terns stay with a previous partner although pair bond duration does not affect breeding output - Maren Rebke; Peter H. Becker; Fernando Colchero (2017)
Supplementary methods, supplementary discussion, supplementary tables and supplementary figures